Akibat Hukum Penggunaan Akta Kuasa Mutlak Sebagai Dasar Akta Jual Beli - Mustika, Devana (Universitas Ekasakti, 2023)
A deed is a writing that is deliberately made to be used as evidence of an event (deed, agreement, or decree) and is signed. In carrying out an act, a person can give authority to another person to carry out the matter, namely to an institution of power. The existence of a power of attorney makes human life easier, but not all matters can be done with power of attorney, there are things that are prohibited by statutory regulations, one of which is the use of power of attorney in the transmission of land rights. The problem raised in this research is the legal consequences of transferring land rights through a sale and purchase based on an absolute power of attorney deed. To answer this problem, the research method used is juridical-normative. The data collection tool in this research is through document study obtained from various regulatory sources that apply in Indonesia. The final part of this research concluded that the legal consequences of using an absolute power of attorney deed in the process of changing the name of a certificate are null and void, this is because the debt acknowledgment letter which is an inseparable unit with the absolute power of attorney deed does not have an executorial title and does not meet the objective requirements of the validity of an agreement.